Transcriptomes of post-mitotic neurons identify the usage of alternative pathways during adult and embryonic neuronal differentiation. (December 2015) - Tallafuss, Alexandra; Kelly, Meghan; Gay, Leslie; Gibson, Dan; Batzel, Peter; Karfilis, Kate; Eisen, Judith; Stankunas, Kryn; Postlethwait, John; Washbourne, Philip
Abstract Background Understanding the mechanisms by which neurons are generated and specified, and how they integrate into functional circuits is key to being able to treat disorders of the nervous system and acute brain trauma. Much of what we know about neuronal differentiation has been studied in developing embryos, but differentiation steps may be very different during adult neurogenesis. For this reason, we compared the transcriptomes of newly differentiated neurons in zebrafish embryos and adults. Results Using a 4tU RNA labeling method, we isolated and sequenced mRNA specifically from cells of one day old embryos and adults expressing the transgeneHA-uprt-mcherry under control of the neuronal markerelavl3 . By categorizing transcript products into different protein classes, we identified similarities and differences of gene usage between adult and embryonic neuronal differentiation. We found that neurons in the adult brain and in the nervous system of one day old embryos commonly use transcription factors - some of them identical - during the differentiation process. When we directly compared adult differentiating neurons to embryonic differentiating neurons, however, we found that during adult neuronal differentiation, the expression of neuropeptides and neurotransmitter pathway genes is more common, whereas classical developmental signaling through secreted molecules like Hedgehog or Wnt are less enriched, as compared to embryonic stages. Conclusions We conclude that both adult and embryonic differentiating neurons show enriched use of transcription factors compared to surrounding cells. However, adult and embryonic developing neurons use alternative pathways to differentiate. Our study provides evidence that adult neuronal differentiation is distinct from the better characterized embryonic neuronal differentiation process. This important insight and the lists of enriched genes we have identified will now help pave the way to a better understanding of the mechanisms of embryonic and adult neuronal differentiation and how to manipulate these processes.